Wage Inequality and Labor Rights Violations - Ioana E. Marinescu; Yue Qiu; Aaron Sojourner (Institute of Labor Economics (IZA), 2021)
Wage inequality does not fully capture differences in job quality. Jobs also differ along other key dimensions, including the prevalence of labor rights violations. We construct novel measures of labor violation rates using data from federal agencies. Within local industries over time, a 10% increase in the average wage is associated with a 0.15% decrease in the number of violations per employee and a 4% decrease in fines per dollar of pay. Reduced labor market concentration and increased union coverage rate are also associated with reductions in labor violations. Overall, labor violations are regressive: they increase inequality in job quality.
Keywords: J31; J83; J32; J33; J28; K31; K42; 330; wage differentials; inequality; worker power; labor rights